Counseling : A Retention Initiative in Open University Malaysia - Mohammad Noor Salleh; Latifah Abdol Latif; Ramli Bahroom; Zainal Abidin Ahmad; Mohd Jamaludin Muhammad (2006)
Learner support services play a pivotal role in the retention and success of learners in any higher education institution. One particular area of such a service is academic advising and counseling. In Open University Malaysia (OUM), the Counseling Unit which operates under the Centre for Student Affairs plays a key role in encouraging learners to participate fully in their academic life and going through a holistic experience while they grow both intellectually and emotionally. One of the strategic thrusts of OUM for 2005 is learner retention. Presently, the overall learner retention rate stands at approximately 80%. Though the figure is reasonably high, OUM should strive to take proactive measures in minimizing the barriers to learner retention and increase academic interests. OUM pays particular attention to “at- risk” (with a CGPA < 2.0) learners by providing counseling services to help them cope better in their studies, until completion or graduation. The counseling unit conducts learning skills workshops for “at- risk” learners with a view of improving academic performance. The paper reports on (i) the findings of the workshop with respect to the factors that purportedly affect academic performance; (ii) the modules developed to help learners overcome their problems; and (iii) the overall effectiveness of the counseling workshops. The results show that the workshops have been beneficial to “at-risk” learners and have helped them improve their academic performance. (Author's abstract)